Development of a Brain-Computer Interface (BCI) for person with disabilities to control their wheelchair using brain waves along with health monitoring system - Salim Rafid, Sk Tahmed; Miazee, Redwan Ahmed; Byzid, Md. Kutubuddin; Anika, Afsana Anjum (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.